A Comparison of Public Perceptions of Mangrove Ecotourism Management in Urban Coastal Areas: A Case Study of Tangerang, Jakarta, and Bekasi - Salman Rafi; Gatot Yulianto; Fery Kurniawan (International Journal Labs, 2026)
Mangrove ecotourism is one of the efforts to manage coastal areas based on conservation involving local communities. This study aims to analyze and compare public perceptions of mangrove ecotourism management in Ketapang Urban Aquaculture, TWA Angke Kapuk, and Saung Alas. The study used a descriptive quantitative method by distributing questionnaires to 135 respondents using the Likert scale. The data were analyzed descriptively to determine the level of public perception of the management, knowledge, participation, and attitude of the community towards mangrove ecotourism. The results of the study showed that Ketapang Urban Aquaculture obtained the highest perception value of 72.96%, followed by Saung Alas at 72.29%, and TWA Angke Kapuk at 70.89%. All three regions are included in the high perception category. The public generally has a positive perception of mangrove conservation, the ecological function of mangroves, and the development of sustainability-based ecotourism. However, community involvement in decision-making is still relatively low in some areas. In general, the high public perception shows support for sustainable mangrove ecotourism management in urban coastal areas.